The association between low serum vitamin D level & periodontal diseases in Bangladeshi population- An observational study - Rinku, Shaikh Ahmed; Afroz, Jahan Sadia; Sadat, S M Anwar; Barma, Paromita; Kabir, Md Humayun (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Aims: Bangladeshi population (20-45 age) presents early loss of tooth without any history of systemic disease. Low serum vitamin D level is one of the factors of early tooth loss. The aim of the study is to assess the significance of low or insufficient serum vitamin D level as a factor of early tooth loss in Bangladesh perspective. Materials and Methods: An observational study was performed in dental unit of TMSS Medical College from January 2021 to December 2022 after ethical clearance of IRB of this institute. Total number of patients was 70 selected by non-random sampling (judgment sampling) who fulfilled the inclusion and exclusion criteria. We assessed the variable like gingivitis, periodontal pocket & tooth mobility clinically. The depth of the periodontal pocket & gingivitis was assessed by the periodontal probe & the mobility by using a blunt instrument & feel with the fingers before & after Vit D supplementation. Data were processed and analyzed using computer software SPSS version 26.0. Results: Deficiency of low serum vit D level has significant effect on periodontal bone resorption and after correction of serum vit D level resulted clinical improvement on periodontal health. Conclusion: Vitamin D deficiency may place subject at risk of developing chronic periodontitis. J Bangladesh Coll Phys Surg 2024; 42: 363-367